Knowledge management: an approach of social media for crisis response management during pandemic Covid-19/ Alwi Mohd Yunus ... [et al.] - Mohd Yunus, Alwi; Seman@Kamarulzaman, Mohd Ridwan; Kamal Rafedzi, Ezza Rafedziawati; Ismail, NorFatimah (Faculty of Information Management, 2021)
This study is set to explore the various fundamentals of KM strategies for social media adoption by organizations in managing crisis. Managing crisis is about managing chaos, therefore, crisis response system needs to quickly provide information and display effective communication content to facilitate control of the situation and coordinate communication among volunteers, formal organizations and government agencies for a more collaborate functions. This study corresponds to findings that social media can be seen as an effective sharing and dissemination of crisis communication and enabling technology for knowledge transfer and knowledge capture. The findings from this study contribute to understanding the potentials of social media use for a larger functions in crisis support.